2018
DOI: 10.1002/hed.25131
|View full text |Cite
|
Sign up to set email alerts
|

Presence of lytic Epstein‐Barr virus infection in nasopharyngeal carcinoma

Abstract: We developed a simple and reproducible method to simultaneously detect mRNA and protein in formalin-fixed paraffin-embedded tissues of NPC. As a single staining, traditional EBER continues to be useful; however, for interpretation of the phenotype of EBV-infected cells, RNAscope is superior. Significantly, we showed that lytic EBV infection took place in NPC tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
(38 reference statements)
1
18
0
Order By: Relevance
“…Further analysis by cell lineage markers revealed that the majority of cells expressed CD20 (>85%), which is indicative of B cell lineage ( Figure 1A ), with smaller populations of cells that expressed pan-cytokeratin (<5%) or CD3 (<10%) ( Figure 1B ). To establish the presence of EBV and to characterize its replication cycle in the CD20+ subpopulation, we exploited chromogenic EBER-ISH as well as fluorescent EBER-ISH and BRLF-ISH assays, which detect gene products specific to latency and lytic transcriptional programs[17,18]. These assays revealed that although latent infection was predominant, the virus also underwent spontaneous lytic reactivation in B cells at unusually high levels ( Figures 1A and 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further analysis by cell lineage markers revealed that the majority of cells expressed CD20 (>85%), which is indicative of B cell lineage ( Figure 1A ), with smaller populations of cells that expressed pan-cytokeratin (<5%) or CD3 (<10%) ( Figure 1B ). To establish the presence of EBV and to characterize its replication cycle in the CD20+ subpopulation, we exploited chromogenic EBER-ISH as well as fluorescent EBER-ISH and BRLF-ISH assays, which detect gene products specific to latency and lytic transcriptional programs[17,18]. These assays revealed that although latent infection was predominant, the virus also underwent spontaneous lytic reactivation in B cells at unusually high levels ( Figures 1A and 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Fourthly, we also re-examined sections of the NPC biopsy using RNAscope in situ hybridization assays with single-molecule sensitivity for detecting EBV-specific gene products [1719], and observed that EBER-ISH signals were exclusively detected on pan-cytokeratin cells but absent on CD45+ lymphocytes. Finally, by parsing the whole-genomes of EBV isolates from the original NPC biopsy, xenograft, and cell line, we were able to ascertain that these three EBV isolates exhibit homologous sequences at highly discriminative genomic loci such as the genes encoding the nuclear antigens (EBNA-2 , −3, −4, −6) and LMP1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PBMC and tumor samples were obtained from a 69 years old Asian woman (patient A311), nonsmoker, with a lung cancer. Immunohistochemistry for H&E, PD-L1 and EBERish were performed on PFA fixed tissue sections [45]. Tumor single cell suspensions were prepared as previously described [46].…”
Section: Human Samples Immunohistochemistry and Cells Isolationmentioning
confidence: 99%